Reseña: La gestión cultural en la era digital - Antonio Doval Adán (Boletín de la Asociación de Geógrafos Españoles)
Fernández Suárez, G.F., & Fernández Tilve, M.ªD. (Coords.) (2022). La gestión cultural en la era digital. McGraw Hill, 322 pp.